PEMANFAATAN MEDIA SOSIAL DALAM PUBLIC RELATIONS DI SEKOLAH MENENGAH KEJURUAN - Wahyuni, Prima Astri; Ernungtyas, Niken Febrina (Jurnal Komunikasi Nusantara, 2020)
This study aims to analyze social media and public relations that have been implemented at SMK Gema Gawita Tangerang. This research uses a qualitative approach. There were 2 informants of the research informant and interview transcripts were processed. The interview results show that the community prefers to communicate using social media managed by the school to provide information and obtain information to make it easier and more practical. Based on research that has been done, these findings have 3 selective coding namely; Utilization of Social Media, Communicating with the Public, and Reactions Generated.